Commodification and expansion of informal tenancy in the informal settlements of Buenos Aires, Argentina - Rodríguez, María Carla (Revista INVI, 2018)
The widespread presence of informal settlements has historically characterized the growth and consolidation process of Latin American cities. Initially, these self-production methods placed priority on the satisfaction of basic needs; however, the progressive consolidation experienced by these spaces triggered the emergence of informal commodification models to secure access to land and housing, such as tenancy. This paper aims to characterize the dynamic that governed the informal tenancy process in different settlements of Buenos Aires over the last decade by analyzing the profiles of relevant actors (tenants, offering parties and mediators) and the forms adopted by tenancy on a daily basis (circuits, conditions and economic agreements.) The cases analyzed in this paper (Settlement 31 and 31 bis, 20, 3, 21-24 and Rodrigo Bueno, all built on public lands) reveal a growing heterogeneity among actors and agreements that consolidate, through practices, a private land appropriation process and the exacerbation of intra-territorial inequalities, thus posing a challenge to rights-based urban policies.